THE NEW (ATHEIST) WOMAN: A LEGACY OF THE 1960S CULTURAL REVOLUTION? - Eccles, Janet (Society Register, 2017)
It is undoubtedly true that a number of British women turned their back on religion, from the beginning of the period of the cultural revolution of the 1960s and onwards. To what might we attribute these defections and the taking up of a new nonreligious identity? Was it the change in sexual mores and the rise of second wave feminism, the increase in women entering higher education opening up new worldviews to them or increasing affluence? This article examines a variety of factors through the eyes of self-identified women atheists/humanists most of whom have lived through that period. It notes that, while these factors may well be significant to different degrees for different women, the turn to atheism, specifically, results largely from women having been damaged by religion and the deep emotional impact thus left behind. The turn to atheism is not a uniform experience as the women are enmeshed in differing types of ‘emotional regime’ which affects how they respond.